Students Metacognitive Level on Solving Chemistry Problems - Burhanudin Milama; Ade Ira Nurjanah; Dila Fairusi (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2017)
Abstract Metacognitive is knowledge and understanding of the cognitive process or knowledge of mind, and it’s work. Metacognitive is needed on solving the problem. Every student has different metacognitive abilities. This research is to describe students metacognitive level on solving chemicals molarity problem. This research was held in SMAN in South Tangerang, by 104 students as the subject research. This research is a quantitative descriptive by the essay results as the data. This result is analyzed, and the metacognitive level is stated based on the indicators. As the results of this research are 14.42% students are in Aware Use level, 73.08% in metacognitive Strategic Use level and 12.50% in metacognitive Reflective Use level. Metacognitive Reflective Use is the level for the high score students. Metacognitive Strategic Use is for middle score students. And metacognitive Aware Use for the low score students. Metacognitive Strategic Use level as the average. Most of the students can use and realized the right strategy on solving problems. Male students have a metacognitive level that is higher than for women. Abstrak Metakognitif adalah pengetahuan dan kesadaran tentang proses kognisi, atau pengetahuan tentang pikiran dan cara kerjanya. Dalam memecahkan masalah kimia, memerlukan keterlibatan metakognitif. Setiap siswa memiliki kemampuan metakognitif yang berbeda-beda. Penelitian ini bertujuan untuk mendeskripsikan level metakognitif siswa dalam memecahkan masalah pada materi kelarutan dan hasil kali kelarutan. Penelitian ini dilakukan di SMA Negeri di Tangerang Selatan dengan subjek penelitian sebanyak 104 siswa. Penelitian ini merupakan penelitian deskriptif kuantitatif sehingga datanya berupa hasil tes essai. Hasil tes essai tersebut dianalisis dan ditentukan level metakognitifnya berdasarkan indikator yang telah dibuat. Hasil yang diperoleh dari penelitian ini adalah sebanyak 14.42 % siswa berada pada level metakognitif Aware Use, sebanyak 73.08 % siswa berada pada level metakognitif Strategic Use dan sebanyak 12.50 % siswa berada pada level metakognitif Relective Use. Siswa yang memiliki hasil belajar yang tinggi di dalam kelas berada pada level metakognitif Reflective Use. Siswa yang memiliki hasil belajar yang sedang di dalam kelas berada pada level metakognitif Strategic Use. Dan siswa yang memiliki hasil belajar yang rendah di dalam kelas berada pada level metakognitif Aware Use. Rata-rata level metakognitif siswa berada pada level metakognitif Strategic Use, karena rata-rata siswa dapat menggunakan dan menyadari strategi yang tepat dalam menyelesaikan masalah, tidak hanya mampu memahami masalah. How to Cite : Nurjanah, A., I. Milama, B. Fairusi, D. (2017). Students Metacognitive Level on Solving Chemistry Problems. TARBIYA: Journal of Education in Muslim Society, 4(1), 63-73. doi:10.15408/tjems.v4i1.5846. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.5846